Experimental Study of Crack Growth Arrest Using Stop-Drilled Hole (SDH) with Pre-Stress - Yudi Dwianda; Tulus Swasono (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
When critical cracks are detected, the choice of one or a combination of repair techniques to be used depends on many factors, such as crack conditions, expected precision, type of material, availability of tools and experience required. One method is to make Stop-Drilled Hole (SDH) at the ends of the crack. This research examines crack growth arrest in the form of Stop-Drilled Hole. Variation was given the initial stress (Pre-Stress) with a combination of variations in the size of the SDH. This combination has a varied effect on the average critical load that can be held before cracking propagates. In this study, it was found that the greater the dimensions of the SDH, the average critical load needed to re-propagate the crack also increases. It was also found that the initial stress applied to the SDH would raise the average value of the critical load.